Perancangan Sistem Pengendalian Manajemen Berbasis Digital pada Himawari Education Batam - Fennesy Fiorent Lim; Serly Serly (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to design and implement a digital-based management control system at Himawari Education Batam. The main problem faced by the institution is the continued use of manual administrative and learning management systems, which has resulted in low efficiency in data management, internal communication, and learning evaluation as the number of students increases. The methods applied in this activity include observation, interviews, and documentation. Based on the data collected, a digital management control system was designed by utilizing Microsoft Teams for internal communication, classroom management, document storage, and meeting minutes; Google Form for student data collection and student registration; and Wordwall as an interactive learning medium to create a more active classroom atmosphere. The results indicate that the implemented system improves administrative efficiency, enhances coordination between teachers and management, and supports a more engaging and interactive learning process. The use of Wordwall is also proven to increase students’ learning motivation. This activity implies that the integration of simple digital platforms can support digital transformation and improve service quality at Himawari Education Batam.